Myositis-associated antibodies and interstitial lung disease - Nishimi, Shinichiro; Wakabayashi, Kuninobu (Journal of The Showa University Society, 2023)
Polymyositis （PM） and dermatomyositis （DM） are often complicated by interstitial lung disease （ILD）. In recent years, the clinical course was found to differ depending on the type of myositis-related autoantibodies. Anti-aminoacyl tRNA synthetases （ARS） antibodies are autoantibodies that present with clinical manifestations called anti-ARS antibody syndromes, such as myositis, fever, polyarthritis, interstitial pneumonia, Raynaud’s phenomenon, and mechanic’s hands. High-resolution computed tomography and pathological findings often show a nonspecific interstitial pneumonia pattern but some cases are accompanied by infiltrative opacities. Currently, eight types of anti-ARS antibodies have been identified with different phenotypes depending on the type. Anti-melanoma differentiation-associated gene 5 （MDA5） antibody is an autoantibody whose corresponding antigen is a protein called MDA5 which is involved in defense against infection. Muscle symptoms are limited in patients positive for this antibody, but they show a pattern of diffuse alveolar damage on imaging for several days. It frequently complicates rapidly progressing ILD leading to respiratory failure over several weeks. The treatment algorithm regarding ILD, which will merge with PM/DM in 2020, is proposed in the “Diagnosis and treatment guidelines for interstitial lung diseases associated with connective tissue disease,” which was jointly created by the Japanese Respiratory Society and the Japanese Society of Rheumatology. Triple therapy with high-dose prednisone, including steroid pulse therapy, a calcineurin inhibitor, and intermittent high-dose cyclophosphamide, was recommended from the beginning, especially for patients positive for the anti-MDA5 antibody. In recent years, new treatment methods, such as plasma exchange therapy, have been used in cases where even these three-drug combination therapies were ineffective.